Inclusive sports management criteria for children with Down syndrome from private subsidized schools in the Talcahuano region. (Revista horizonte, 2016)
Inclusion is a cross-cutting phenomenon worldwide and Chile is not an exception. That is why courses of action have been taken to break down barriers affecting disabled people. The objective of this research is to investigate the criteria guiding inclusive sports management in primary school children with Down Syndrome (SD) of state-subsidized schools in Talcahuano County. Methodology: A questionnaire of 22 closed questions was answered by the heads of the Educational Technical Unit (UTP) of the schools on research. The results indicate that the restricted access for the disabled are appropriate in most of the schools, a non-discrimination adherence is present and a thorough knowledge of the population with DS exists. However, communication between the board staff and the working team is weak and so is the continuous improvements issue. It is concluded that there is no formal model of inclusive sports management for children with DS but only some developed criteria of excellence inclusive management are present.